Donation programme of returned medicines: role of donors and point of view of beneficiaries. Issue 2 (1st February 2018) - Nicoli, Francesco; Paudel, Deepak; Bresciani, Giulio; Rodi, Donata; Siniscalchi, Anna
Abstract: Background: Donation of returned medicines is a debated health policy issue as it is discouraged by WHO, but accepted in some countries. Methods: Lessons learned from a donation programme of returned medicines carried out in Europe were documented. Results: The donation programme we reviewed followed a strict protocol for collection, sorting and distribution of returned drugs, in order to avoid the major limitations associated with unused medicine donations. Over a period of 3 years, 23 145 boxes of medicines were donated to 14 organizations operating in Europe, Africa and Latin America. Conclusions: The donations covered about one-third of the volume of medicines used by beneficiary organizations. The programme helped to decrease expenditure by both patients and health facilities.